Addressing ‘Loss and Damage’ For Climate Justice in The Global South: An Analysis - Jahan, Noor Israth (Kathmandu School of Law Review, 2025)
Determining climate related loss and damage and identifying historical responsibility for it is a highly debated topic in the climate change discourse. There are various critical aspects to this issue - agreeing on the contours and criteria of what ‘loss and damage’ is, acceptance of historical responsibility by big emitters, fixing compensation for the loss and damage, and the encompassing concern of equity and justice. A proper resolution of the issue must also account for the justice concerns of developing and small island states who, though having contributed the least in creating the climate change problem, are the most affected victims of loss and damage due to their geographical location, climatic conditions and limited adaptive capacities. Since the beginning of the United Nations Framework Convention on Climate Change (UNFCCC) negotiations, developed and developing countries have struggled to frame the concept of loss and damage, and the issue remains. This article explores how developed countries have succeeded in containing progression of the concept of loss and damage and avoiding ‘historical responsibility’ for it. The launch of the Loss and Damage Fund in UNFCCC Conference of Parties 28 is no doubt a milestone for developing countries, but its constitution as a voluntary fund without compulsory contribution from the well-known and highest emitters creates skepticism as to whether it will bring any justice for the Global South. By employing an analytical method and examining both primary and secondary sources, this article concludes that the current framing of the loss and damage issue is unlikely to usher in climate justice for the Global South because it does not associate climate related loss and damage with historical responsibility of the carbon polluters – without their association, a liability framework will not take off.